2017
DOI: 10.1371/journal.ppat.1006195
|View full text |Cite
|
Sign up to set email alerts
|

Early endonuclease-mediated evasion of RNA sensing ensures efficient coronavirus replication

Abstract: Coronaviruses are of veterinary and medical importance and include highly pathogenic zoonotic viruses, such as SARS-CoV and MERS-CoV. They are known to efficiently evade early innate immune responses, manifesting in almost negligible expression of type-I interferons (IFN-I). This evasion strategy suggests an evolutionary conserved viral function that has evolved to prevent RNA-based sensing of infection in vertebrate hosts. Here we show that the coronavirus endonuclease (EndoU) activity is key to prevent early… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
263
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(284 citation statements)
references
References 65 publications
20
263
1
Order By: Relevance
“…The ability of coronaviruses to remain undetected by innate immune sensors has been unraveled recently. 40 Interestingly, for most viruses that affected cilia beating and MCC, a limited number of cells was infected, and the ciliated cell layer was preserved. This observation suggests a paracrine effect, propagated disorganization of cilia beating, or both.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of coronaviruses to remain undetected by innate immune sensors has been unraveled recently. 40 Interestingly, for most viruses that affected cilia beating and MCC, a limited number of cells was infected, and the ciliated cell layer was preserved. This observation suggests a paracrine effect, propagated disorganization of cilia beating, or both.…”
Section: Discussionmentioning
confidence: 99%
“…Although all tested endoribonuclease of nidoviruses have been demonstrated to antagonize IFN production, it is still inconclusive whether this function fully depends on its endoribonuclease activity. Several studies showed that overexpression of WT nsp15 s of CoV or nsp11 s of arterivirus significantly suppressed IFN production, while the mutants lacking endoribonuclease activity lost this capacity (Kindler et al, 2017;Shi et al, 2011;Sun et al, 2016). These evidences appear to indicate that the endoribonuclease activity is essential for nsp15/ nsp11-mediated inhibition of IFN production.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is appears that different mechanisms are utilized by the endoribonucleases from different nidoviruses. For example, the nsp15 s of MHV and HCoV-229E prevent the activation of IFN response by mediating the evasion of host recognition of viral dsRNA (Deng et al, 2017;Kindler et al, 2017); PRRSV nsp11, the orthologue of CoV nsp15, antagonizes type I IFN production by suppressing both MAVS and RIG-I expression . SARS-CoV nsp15 antagonizes type I IFN production by inhibiting MAVS-induced apoptosis (Lei et al, 2009), however, MERS-CoV nsp15 does not utilize this strategy although it also inhibits type I IFN production with a yet-to-be identified mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…In common with other coronaviruses, the MERS-CoV nsp3 PLpro removes ubiquitin (Ub) (deubiquitination; DUB), and interferon-stimulated gene 15 (ISG15) (deISGylation) from host cell proteins, which in turn blocks production of IFN-β and hence reduces type-1 interferon responses in cell line studies (Báez-Santos et al, 2014;Daczkowski et al, 2017). MERS-CoV nsp15, which contains an endonuclease (EndoU) activity, has also been recently shown in primary cell lines and in macrophages to reduce early innate immune responses by inhibition of MDA-5, PKR and OAS responses and IFN activation (Kindler et al, 2017). Nsp16, a viral 2'O-methyltransferase (2'O-MTase), has also been recently implicated in viral pathogenesis and type I-IFN inhibition in both primary human airway cell cultures and in vivo mouse models (Menachery et al, 2017a).…”
Section: Innate Immune Response: Interferonmentioning
confidence: 99%